Impact of Violence against Women on Sexual and Reproductive Health: Research Protocol and Results from a Pilot Study - Loreto Mendoza-Huertas; Nicolas Mendoza (IMR Press, 2022)
Objectives: Violence against women (VAW) is associated with a deterioration of endocrine function with consequences similar to those of premature ovarian failure in women. The main objective of this study is to evaluate the hormonal repercussions of VAW and, secondly, to analyse the cardio-metabolic, bone, cognitive, psychological, and psychosexual consequences of hypoestrogenism secondary to VAW. Materials and Methods: A cross-sectional study will be conducted on women of any age who have suffered VAW at some point in their lifespan, whether psychological, sexual, or physical. Clinical, hormonal, cardio-metabolic, bone, psychological, and psychosexual parameters will be analysed. Results: The pilot study from the first 23 women show that all of them are suffering from severe sexual dysfunction. In addition, all women reported menstrual irregularity and hypoestrogenism (including two cases of premature ovarian failure) since the VAW episode. Conclusions: VAW is a pandemic that affects all women equally, regardless of their age, status, social background, or education. Despite the claims made by certain groups, VAW does not depend on women, but rather it affects women and is clearly harmful to their sexual, reproductive, and general health.